KERANGKA KERJA PERENCANAAN PENGEMBANGAN PRODUK SEBAGAI PENINGKATAN DAYA SAING INDUSTRI KECIL MENENGAH - Broto Widya Hartanto; Subagyo Subagyo (Universitas Gadjah Mada, 2018)
This study developed a new product development planning framework for small and medium enterprise (SME) in creative industry sector to increase the business competitiveness. The development process referred to the stages of design science research. The development stage adapted the first two stages of the modular function deployment (MFD), those are the description stage of consumer need through the house of quality, and functional decomposition. The study explained that the application of MFD adaptation is effective and adequate to the creative SME condition. The technical concepts were able to be screened and scored by using pugh selection matrix. However, every technical concepts could not be described into detailed domain functions and means. Therefore, the addition of methods applied in parallel was carried out, that is the concept decomposition with the function means tree, and the technical solution synthesis with the axiomatic design so that the design process is easier to handle. It’s recommended to eliminate the zigzagging process in axiomatic design, since it has been done on the function means tree and the use of customer relationship management data base to support voice of customer.